Octacoordinate metal carbonyls of scandium and yttrium: theoretical calculations and experimental observation. (7th May 2013) - Xing, Xiaopeng; Wang, Jie; Xie, Hua; Liu, Zhiling; Qin, Zhengbo; Zhao, Lijuan; Tang, Zichao
Abstract : RATIONALE: The transition metal carbonyls are among the most important complexes in coordination chemistry. The maximum coordination number in these complexes is seven. Because the cations Sc + and Y + have empty second outermost d orbital subshells, they can possibly bond eight CO ligands, forming the 18‐electron d 10 s 2 p 6 noble gas configuration. The aim of this study is to determine whether the octacoordinate metal carbonyls of Sc + and Y + exist. METHODS: The structures and bonding of M(CO) n + (M = Sc and Y, n = 7–9) were studied using Density Functional Theory (DFT) calculations with the functionals of B3LYP and BP86. The cationic complexes from laser ablation of Sc and Y in CO gas were analyzed by time‐of‐flight mass spectrometry. RESULTS: The structures of M(CO) n + (M = Sc and Y, n = 7–9) and the bond dissociation energies for the last CO ligand in M(CO) n + (M = Sc and Y, n = 8 and 9) were obtained using DFT calculations. The products in the experiment for both metals include the series MO(CO) n +, MO(H2 O)(CO) n + and M(CO) n + (M = Sc or Y). The intensities of the MO(CO) n + and MO(H2 O)(CO) n + ions change gradually with the number of CO ligands, while most M(CO) n + ions are very weak except for three intense ones, Sc(CO)7 +, Sc(CO)8 + and Y(CO)8 + . CONCLUSIONS: Comparisons between the theoretical calculations and the experimental observations indicate that eight CO ligands are chemically bonded on the central atom in the singlet state of Sc(CO)8 + ( 1 A1 state of D 4 d symmetry) and the singlet and triplet states of Y(CO)8 + ( 1 A1 state of D 4d symmetry and 3 A1g state of Oh symmetry). The 1 A1 states of both Sc(CO)8 + and Y(CO)8 + have the 18‐electron d 10 s 2 p 6 noble gas configuration. In M(CO)9 + (M = Sc or Y), the ninth CO is weakly adsorbed on the external shell. Copyright © 2013 John Wiley & Sons, Ltd.